Device Simulation of Si-Ge HBT Using SILVACO TCAD - Pandey, Kamal Prakash (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we have proposed a Si-Ge HBT Using Silvaco TCAD. In recent years, the band gap engineered devices have received considerable attention due to their inherent advantages such as high speed and high driving capability as compared to homo junction devices. The Si-Ge Hetero junction Bipolar Transistor (HBT) is the first band gap engineered device to be developed on Si. The recent advancement in material growth technology and device design has resulted in Si-Ge HBT’s operating at more than 250GHz cutoff frequency. The present paper deals with the simulation of Si-Ge HBT structures using Silvaco TCAD. HBT structure has been generated through DevEdit and device simulation was carried out using Atlas. Base width and Ge profile are very important parameter for HBT. In view of this, the effect of variation of base width and Ge profile on the parameters like Collector Current (Ic), Current Gain (β), fT and fmax has been studied.